Risk Factors Associated with Multivessel Coronary Artery Disease: A Cross Sectional Study - Firdaus, Zulfian; Putra, Muhammad Faqih Dwi; Tanjung, Suyata Adelina; Saragih, Robert E. (Syntax Corporation Indonesia, 2026)
Cardiovascular disease (CVD) is the highest cause of death globally, with coronary artery disease (CAD) as its manifestation. Multivessel disease (MVD), which involves two or more coronary vessels, has a higher risk of major cardiovascular events and long-term mortality than single-vessel disease (SVD). This study aims to determine the significant risk factors for the occurrence of MVD. The retrospective cross-section research design was carried out by analyzing medical record data of 122 patients who underwent coronary angiography (CAG) at Karawang Hospital in June-December 2023. Chi-square analysis was used for the identification of risk factors associated with MVD, and variables with p<0.025 were further analyzed using multivariate logistic regression. Results showed that diabetes mellitus (62.3%) and hypertension (50.0%) were the main risk factors, with a significant association between the two with the incidence of MVD (p=0.019 for hypertension, p=0.022 for diabetes). Logistic regression revealed that diabetes mellitus (OR=3.06; p=0.027) and hypertension (OR=3.72; p=0.015) were independent predictors of MVD incidence. Dyslipidemia showed no significant association (OR=1.89; p=0.271), likely as a result of the use of statin therapy. These findings confirm the importance of early detection, control of metabolic risk factors, and lifestyle modification in the prevention of MVD.